A New Look at the pds.t-n.t-nbw of Zauberspru?che fu?r Mutter und Kind, Spell P - Cahail, Kevin M..
Since Erman’s rst edition of the Zauberspru?che fu?r Mutter und Kind, translators have never adequately explained the meaning behind the phrase pds.t-n.t-nbw, appearing in Spell P. Understanding the form of this amulet, meant to protect a child from sickness brought about by poison, is integral to a new interpretation of the Zauberspru?che fu?r Mutter und Kind Spell P. This paper begins with an analysis of the various attestations of the term pds.t, and then offers a new translation of Spell P. The main focus then shifts to a detailed examination of the archaeological and textual sources connected with the Spell P ritual, in order to understand the form of the pds.t-n.tnbw amulet, and how it, and the other amulets mentioned in Spell P, all served to remove poison from the body.